Thrust faults and extensional detachment faults in Cretan tectono-stratigraphy: Implications for Middle Miocene extension - Papanikolaou, Dimitrios; Vassilakis, Emmanuel (Tectonophysics, 2010)
The revised tectono-stratigraphy of Crete and especially of the "Phyllites-Quartzites" complex demonstrated the distinction of the probable Paleozoic low-medium grade metamorphic rocks of the Arna unit from the underlying Permo-Triassic phyllites and associated carbonate sediments (Trypali facies) of Western Crete unit as well as the overlying Permo-Triassic phyllites and associated sediments of the Tyros/Ravdoucha Beds at the base of the Tripolis unit. The pre-existing mixture of the above tectono-stratigaphic units in a single complex created a number of misinterpretations as far as stratigraphy, metamorphism and interpretation of low angle faults as thrusts or detachments. Especially in cases where the inferred tectonic contact concerns the transition between the Tyros Beds and the base of the Tripolis carbonate platform there is no structural omission and therefore the contact represents a minor disharmonic sliding surface and not a detachment. Based on the revised tectono-stratigraphic analysis the determination of the structural omission for each tectonic contact was possible and several detachments were described for the first time. Footwall rocks of the detachments comprised several tectonic units usually from the lower nappes and hanging wall rocks comprised several tectonic units usually from the upper nappes. The detachment may separate not only metamorphosed units in the footwall (Mani, Western Crete, Arna) from non metamorphosed units in the hanging wall (Tripolis, Pindos and higher nappes) but also all other possible combinations from the Cretan nappe pile. Extension in Crete started in the Middle-Late Miocene with the formation of extensional detachment faults. The reported extensional structures of Oligocene to Early Miocene age do not correspond to crustal extension of Crete but to localized shear zones related to nappe stacking and the exhumation of metamorphic rocks. Extensional detachments in Crete form a tectonic horst through two oppositely dipping E-W-trending zones; one dipping north, related to the opening of the Cretan basin, and the other dipping south, related to the formation of the Messara supra-detachment basin. The deformation history of units within Crete can be summarized as: (i) compressional deformation producing arc-parallel east-west-trending south-directed thrust faults in Oligocene to Early Miocene time; (ii) extensional deformation along arc-parallel, east-west-trending detachment faults in Middle Miocene time, with hanging wall motion to the north and south; and (iii) Late Miocene-Quaternary transtensional deformation along high-angle normal and oblique normal faults that disrupt the older arc-parallel structures.
Keywords: Aegean Sea; Crete Island; Crustal extension; Detachment; Hellenides